Establishing paediatric reference intervals for thyroid function tests in Croatian population on the Abbott Architect i2000 - Bokulić, Adriana (Array, 2021)
Evaluation of thyroid function is often requested and therefore defining paediatric reference intervals (RIs) is of vital importance. Currently, there is a distinct lack of paediatric RIs for thyroid function tests in Croatia. Thus, we established RIs for thyroid stimulating hormone (TSH), total triiodothyronine (TT3), total thyroxine (TT4), free triiodothyronine (FT3) and free thyroxine (FT4) in the Croatian paediatric population. Reference intervals were calculated from 397 apparently healthy children, aged from 2 days to <19 years. Serum samples were analysed for thyroid function tests on the Abbott Architect i2000. Age- and sex-specific 95% RIs with 90% confidence intervals were established according to Clinical and Laboratory Standards Institute guidelines. To express the magnitude of sex and age variation, standard deviation ratio (SDR) was calculated using two-level nested ANOVA. The criterion for considering partitioning reference values was set to SDR >0.3. All thyroid function tests required age partitioning, confirmed by SDR above 0.3. There was no need for sex partitioning, confirmed by SDR below 0.3. Still, FT3 was partitioned due to visually noticeable sex related difference for the oldest group (12 years to <19 years). This is the first study to establish RIs for thyroid function tests in the Croatian paediatric population. We propose RIs for widely used Abbott platform, thus giving laboratories method- and population-specific paediatric RIs for thyroid function tests that should improve clinical test interpretation.